Answer: The equation in point slope form is y-6 = x-3
Step-by-step explanation: The general equation of a line in point slope form is y - y1 =m(x -x1)
where m is the slope and (x1,y1) is the point
Given point (3,6) and (-2,1)
We know slope of a line when two points are given
m=
![(y2-y1)/(x2-x1)](https://img.qammunity.org/2019/formulas/mathematics/high-school/im76jry3ymtqnvln3l0t8lo4zqhnce6gfm.png)
where (x1,y1) and (x2,y2) are the two points
Here m=
![(1-6)/(-2-3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/44o9rrd1rv87ass7lmfe9gtqww2oukqfad.png)
=
![(-5)/(-5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/v7kusgnmrrzrx6o6azp0hoel0ksmjw7oci.png)
m=1
Now the equation of line
y-6 = 1 (x-3)
i.e. y-6 = x-3